RECONNAISSANCE ON LIQUEFACTION-INDUCED FLOW FAILURE CAUSED BY THE 2018 MW 7.5 SULAWESI EARTHQUAKE, PALU, INDONESIA - Hidayat, Risqi Faris; Kiyota, Takashi; Tada, Naoto; Hayakawa, Jun; Nawir, Hasbullah (Journal of Engineering and Technological Sciences, 2020)
The Mw 7.5 Sulawesi Earthquake 2018 was a catastrophic disaster that resulted in large numbers of casualties. This study aimed to investigate the damages of liquefaction-induced-flow failure in three areas in Palu city, i.e. Petobo, Balaroa, and Jono Oge. It was found that this flow failure occurred on a large scale at a very gentle ground inclination, ranging from 1 to 3%. In order to gain an understanding of the soil conditions in these specific locations, Portable Dynamic Cone Penetration Tests were conducted in Petobo. The results showed that the soil layers in the affected area were in a loose state compared to the non-affected areas. Furthermore, some spots of freshwater inundation were recognized in Petobo and Balaroa, even two weeks after the disaster. Based on this evidence, a mechanism of liquefaction-induced-flow failure caused by a confined aquifer is proposed.